2019
DOI: 10.18314/ctoy.v2i1.1478
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Annexin A1 Protein in an Infectious Keratitis Model: Therapeutic Perspectives

Abstract: Introduction: bacterial keratitis caused by Pseudomonas aeruginosa is one of the causes of blindness in the world, due to pathogenicity of the bacteria that can lead to corneal perforation. Studies on the protein annexin A1 (AnxA1) point it as one of the essential mediators in homeostasis of inflammation and ocular infections. However, there are no known reports of AnxA1 in keratitis. Objetive: to investigate the expression profile of AnxA1 in the P. aeruginosainduced keratitis model in two strains of mice (su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 42 publications
3
3
0
Order By: Relevance
“…The immunohistochemical analysis of untreated EIU eyes showed an increase in the intensity of immunolabeling for AnxA1, corroborating our previous findings in ocular tissues [17,34] and ocular inflammatory cells [16]. The higher expression of AnxA1 was also observed in neutrophils in ocular toxoplasmosis in mice and culture of retinal pigmented cells infected with Toxoplasma gondii [30].…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…The immunohistochemical analysis of untreated EIU eyes showed an increase in the intensity of immunolabeling for AnxA1, corroborating our previous findings in ocular tissues [17,34] and ocular inflammatory cells [16]. The higher expression of AnxA1 was also observed in neutrophils in ocular toxoplasmosis in mice and culture of retinal pigmented cells infected with Toxoplasma gondii [30].…”
Section: Discussionsupporting
confidence: 88%
“…Although our results indicated that the combination of the peptide with PL promoted a decrease in the effects of Ac2-26, the dosage of 200 µg of PL still allowed the peptide actions in a moderate manner, which may explain the lower expression of the endogenous AnxA1 in this group. Modulation in the expression of AnxA1 after LPS inoculation found in this investigation reinforces the involvement of the protein in ocular tissue physiology during inflammatory [16,17], infectious [34], allergic [32,35], and autoimmune [18,20] processes in experimental models. Interestingly, the expression of AnxA1 remains increased after treatments with PL singly administered or at 400 µg dosage in combination with the peptide.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations